Apoio matricial e institucional: investigando interfaces com a Residência Multiprofissional em Saúde da Família e Comunidade - Beker, Karine Kyomi (Universidade Federal de São Carlos, 2014)
The Family Health Strategy (FHS) is focused on family and community, acting through strategies of promotion, prevention, recovery and rehabilitation. Complementing the actions of family health teams, matrix support consists in an organizational arrangement that offers specialized care as much rear of technical and pedagogical support teams and institutional support is intended to facilitate the spaces of co-management and joint teams, enabling the expansion of capacity and facilitating analysis of the process of reflection on the difficulties of everyday life. The need for training of professionals capable of these changes in health services has encouraged the creation and development of Multiprofessional Residences in Health. The Federal University of São Carlos (UFSCar) and the Municipal Health Secretariat of the municipality proposed the insertion of the Multiprofessional Residence in Health Family and Community (RMSFC) in municipal health network, in which residents work in the logic of FHS. The study aimed to understand the interfaces between activities as supporters and the process experienced in training RMSFC UFSCar. This is a qualitative study and by applying via online, a questionnaire with open and closed to graduates of the period 2007-2012 residency program questions, 21 answers to the questionnaire were obtained. Empirical data were examined using thematic analysis and divided into two themes: support and network school. For each theme, two categories were compiled: matrix support as an activity that focuses on care, the organization of the work process as the focus of institutional support, practical learning scenarios theoretical and practical training and theoretical spaces. The matrix support actions related to health care were assigned, while institutional support refers to the organization of the work process, according to the same. The scenario of practical and theoretical learning as well as the use of tools of lifelong education favor the formation of capable workers to collective actions, presenting augmenting elements for both supports, in particular the matrix. It appears, therefore, that the political pedagogical project (PPP) and the organizational arrangement of the residency program were developed and established in order to promote the full learning on the matrix support. The same is not true with respect to institutional support, for which some gaps should be analyzed. However, if the PPP does not endorse this type of support, the management powers of the work contained in assignments and assessments of residents, includes unique elements of the institutional support. In light of the theoretical framework, discusses the importance of integration between the educational institution and the municipal health system, providing residents an apprenticeship in which practice and theory complement each other. Thus it is apparent that, with this approach, fosters the formation of workers to adequate Unified Health System can affirm that there is an interface between the training process experienced in the residence and the practice of both supports listing, Top basement of the matrix support.
Keywords: Saúde pública; Residência multiprofissional em saúde; Apoio matricial; Apoio institucional; Saúde da família; Sistema Único de Saúde (Brasil); Matrix support; Institutional support; Multiprofessional residence; Professional competence; Education; Family health; Unified health system; CIENCIAS DA SAUDE